Gamify to persuade: A systematic review of gamified sustainable mobility - Simone Bassanelli; Riccardo Belliato; Federico Bonetti; Martina Vacondio; Federica Gini; Lorenzo Zambotto; Annapaola Marconi (Acta Psychologica)
The increasing need to address climate change has intensified efforts to promote green transportation options, such as cycling and public transit. Over the past few decades, gamification—the integration of game-like elements into non-game contexts to motivate and engage people in adopting new behaviors—has emerged as a strategy to encourage the use of sustainable transportation. This literature review examines how gamification has been used to drive the adoption of green transportation. Following the PRISMA methodology, 49 documents were initially screened, leading to a final selection of 14 papers. We analyze the stakeholders involved, the game elements, the external rewards (e.g., financial incentives), and persuasive strategies employed, and the overall effectiveness of these initiatives both in the short and in the long term. We also explore the relationship between game elements and persuasive approaches, offering insights into how they are related. Finally, we propose a research agenda that emphasizes the exploration of different game elements and the need for a multidisciplinary approach to designing gameful systems that promote sustainable behaviors.